General dentist orthodontic practice in foreign legal systems - Ivan Toshio Maruo; Armando Saga; Maria da Glória Colucci; Orlando Tanaka; Hiroshi Maruo (Dental Press Editora, 2012)
OBJECTIVE: General dentist orthodontic practice is a controversial issue and this paper aims to analyze it comparing foreign laws to Brazilian Legal System. METHODS: Regulations and scientific texts concerning orthodontic practice by general dentists, in Portuguese or English language, were sought. RESULTS AND CONCLUSION: Portugal clearly forbids general dentist orthodontic practice; United States of America do not clearly forbid general dentist orthodontic practice, but do regulate and promote campaigns to encourage public to seek specialist service; in Australia and England, corrective orthodontics are offered both by orthodontists and general dentists; it was not possible to evaluate how orthodontic services are provided in Eastern Europe; and the fact that general dentists are forbidden to practice corrective orthodontics in Brazilian Legal System is compatible to other countries policy.